Nutritional requirements, medium utilisation and extracellular enzyme production by the fungus Sphaeropsis sapinea and the use of these and other enzymes in membrane cleanup techniques - Engelbrecht, Jolanda (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.